The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.3390/w15040772
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Soil-Water Characteristic Curves for Different Textural Soils Using Fractal Analysis

Abstract: The soil-water characteristic curve (SWCC) is an essential tool to determine hydraulic and mechanical properties of unsaturated soils. As an inherent influencing factor, soil texture controls the characteristics of SWCCs. Fractal theory can quantitatively describe the physical characteristics of soil. This study used particle size distribution data and water content data contained in the UNSODA2.0 database to explore the fractal characteristics of 12 soil types with different textures under different matrix su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…SMT have a strong positive link with clay content while a negative correlation with sand content. Soil moisture increases gradually as clay content increases and sand content decreases under the same matrix suction (C. Yang et al., 2023). The regions where have higher clay content typically have wetter soil.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SMT have a strong positive link with clay content while a negative correlation with sand content. Soil moisture increases gradually as clay content increases and sand content decreases under the same matrix suction (C. Yang et al., 2023). The regions where have higher clay content typically have wetter soil.…”
Section: Resultsmentioning
confidence: 99%
“…The regions where have higher clay content typically have wetter soil. These humid regions are theoretically more sensitive to drought (C. Yang et al., 2023), leading to higher SMT are detected. There is no discernible relationship between SMT and silt content.…”
Section: Resultsmentioning
confidence: 99%
“…The compression deformation coefficient (δ p ) and soil pore ratio (e i ) were used to investigate the relationship between soil compression deformation and soil moisture content and dry density under different loads. The percentage between the shape variable of the sample and the height of the sample before compression and the soil pore ratio during the compression process can be expressed by Equations (7) and (8). The compressibility and its variation rule under different conditions can be easily and intuitively judged by the compression deformation coefficient.…”
Section: Calculation Of the Compression Deformation Coefficientmentioning
confidence: 99%
“…The compaction of disturbed loess can cause engineering problems such as ground cracking and slope instability [5]. These engineering disasters and geological problems are closely related to moisture in loess [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Freddi et al [54], in their study with a latosol (oxisol), found that soil density had a positive influence on the soil water content due to reduced macroporosity and the redistribution of pore sizes, corroborating the results achieved for the same soil class in this study (Figure 3a). The hydraulic functionality differs for soils with different textures, with microporosity playing an important role in this parameter due to the presence of materials with fine textures, e.g., clay and SOM, showing higher retention capacity when the soil is moistened [55,56].…”
Section: Soil Physical and Chemical Attributesmentioning
confidence: 99%